Systematic Mapping of Empirical Research in Non-Sexist Education Between 1970 and 2020 - Calquin-Donoso, C (UNIV COSTA RICA, EDITORIAL, 2022)
This article investigates the production and circulation of scientific knowledge on non-sexist education between 1970 and 2020 to account for the adopted meanings as a proposal for diagnosis and pedagogical intervention from categories, methods, and ethical positions -politicians. This article investigates the production and circulation of scientific knowledge on non-sexist education between 1970 and 2020 to account for the adopted meanings as a proposal for diagnosis and pedagogical intervention from categories, methods, and ethical positions -politicians. Methodologically, 203 empirical articles were selected through a systematic mapping study from the databases Scielo, Scopus, Web of Science, Taylor & Francis, Jstor, and ERIC. The articles were analyzed in terms of their general description (periodicity, trend of journals, and geographical distribution), the methodologies used, and the topics covered. Moreover, the results show a growing field of research with a focus on English-speaking countries. Likewise, the use of qualitative methodologies with an emphasis on higher education and an increasing interest in secondary education stands out. In conclusion, three hypotheses result from the present research: the evolution of the epistemological and methodological approach to non-sexist education, a research field that fails to institutionalize itself, and the social movements in favor of the portrayal of gender and sexuality in education.